Government Role in Geoscience - The Queensland Way (The Australasian Institute of Mining and Metallurgy, 1990)
Government geoscience may be categorised by objective under three headings: Applied Research for Geoscientific Framework Studies, Resource Inventory, and Technical Advice. In Queensland, the Department of Resource Industries is active in all three categories. Under the program-based management system adopted in 1987, three Programs, namely, Geological Survey, Mineral Resources Development, and Energy Resources Development and Utilisation, have geoscience responsibilities.Prime responsibility for geoscience resides with the Geological Survey Program, which provides a geoscientific framework for mineral and energy exploration and the development of the State. Simply stated, the Program goal is to provide geological information when and where it is required. Geological Survey work also encompasses aspects of resource inventory and technical advice, complementing the work of the other two Programs. This role has a 122 year long tradition, for geoscientists of the Geological Survey have been engaged in investigations designed to facilitate the identification and utilisation of the mineral, water and energy resources of Queensland since 1868.